Metformin: A Possible Option in Cancer Chemotherapy - Chidiebere V. Ugwueze; Odunze J. Ogamba; Ekenechukwu E. Young; Belonwu M. Onyenekwe; Basil C. Ezeokpo (Analytical Cellular Pathology)
Metformin has been used for a long time as an antidiabetic medication for type 2 diabetes. It is used either as a monotherapy or in combination with other antidiabetic medications. The drug came into prominence in diabetes and other conditions with cardiovascular risk after the landmark study of 1995 by the United Kingdom Prospective Diabetes Study which emphasized its importance. However, the drug has been used in experimental trials in various aspects of medicine and pharmacology such as in reproductive medicine, cancer chemotherapy, metabolic diseases, and neurodegenerative diseases. It has been in use in the treatment of polycystic ovarian disease and obesity and is being considered in type 1 diabetes. This study seeks to evaluate the relevance of metformin in cancer management. Different mechanisms have been proposed for its antitumor action which involves the following: (a) the activation of adenosine monophosphate kinase, (b) modulation of adenosine A1 receptor (ADORA), (c) reduction in insulin/insulin growth factors, and (d) the role of metformin in the inhibition of endogenous reactive oxygen species (ROS); and its resultant damage to deoxyribonucleic acid (DNA) molecule is another paramount antitumor mechanism.